A Mixed-Methods Pilot Study of Perinatal Risk and Resilience During COVID-19. (July 2020) - Farewell, Charlotte V.; Jewell, Jennifer; Walls, Jessica; Leiferman, Jenn A.
Introduction/Objectives: National guidelines underscore the need for improvement in the detection and treatment of mood disorders in the perinatal period. Exposure to disasters can amplify perinatal mood disorders and even have intergenerational impacts. The primary aim of this pilot study was to use mixed-methods to better understand the mental health and well-being effects of the coronavirus disease 2019 (COVID-19) pandemic, as well as sources of resilience, among women during the perinatal period.Methods: The study team used a simultaneous exploratory mixed-methods design to investigate the primary objective. Thirty-one pregnant and postpartum women participated in phone interviews and were invited to complete an online survey which included validated mental health and well-being measures.Results: Approximately 12% of the sample reported high depressive symptomatology and 60% reported moderate or severe anxiety. Forty percent of the sample reported being lonely. The primary themes related to stress were uncertainty surrounding perinatal care, exposure risk for both mother and baby, inconsistent messaging from information sources and lack of support networks. Participants identified various sources of resilience, including the use of virtual communication platforms, engaging in self-care behaviors (eg, adequate sleep, physical activity, and healthy eating), partner emotional support, being outdoors, gratitude, and adhering to structures and routines.Conclusions: Since the onset of COVID-19, many pregnant and postpartum women report struggling with stress, depression, and anxiety symptomatology. Findings from this pilot study begin to inform future intervention work to best support this highly vulnerable population.